2020
DOI: 10.2106/jbjs.20.01053
|View full text |Cite
|
Sign up to set email alerts
|

Universal Testing for COVID-19 in Essential Orthopaedic Surgery Reveals a High Percentage of Asymptomatic Infections

Abstract: Background: The long incubation period and asymptomatic spread of COVID-19 present considerable challenges for health-care institutions. The identification of infected individuals is vital to prevent the spread of illness to staff and other patients as well as to identify those who may be at risk for disease-related complications. This is particularly relevant with the resumption of elective orthopaedic surgery around the world. We report the results of a universal testing protocol for COVID-19 in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
2
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(79 citation statements)
references
References 9 publications
1
73
2
3
Order By: Relevance
“…The risk of COVID-19 hospital-associated transmission not only endangers the health of hospitalised patients (who may be already weakened by their underlying medical conditions) and healthcare providers but may also lead to further loss of working force. As transmission from asymptomatic or pre-symptomatic carriers or people with mild or atypical symptoms has been documented [6] and universal screening for SARS-CoV-2 in patients admitted to hospital revealed a high percentage of asymptomatic infections [7,8], screening on the basis of symptoms only seemed unwise.…”
Section: Introductionmentioning
confidence: 99%
“…The risk of COVID-19 hospital-associated transmission not only endangers the health of hospitalised patients (who may be already weakened by their underlying medical conditions) and healthcare providers but may also lead to further loss of working force. As transmission from asymptomatic or pre-symptomatic carriers or people with mild or atypical symptoms has been documented [6] and universal screening for SARS-CoV-2 in patients admitted to hospital revealed a high percentage of asymptomatic infections [7,8], screening on the basis of symptoms only seemed unwise.…”
Section: Introductionmentioning
confidence: 99%
“…All patients admitted to hospital, regardless of diagnosis, were screened for COVID-19 form March 14th on; other authors only tested clinically suspicious cases and it is likely that they may have not detected several asymptomatic cases, as was the case for over one-third of our RT-PCR(+) patients. A study from New York reported a 12% positive rate for SARS-CoV-2 once the universal screening was adopted during the first pandemic wave, with over half of the detected cases asymptomatic at the time of admission [39], and 11% of the patients that tested positive at admission in a multicentric series from London were asymptomatic [40]. Consequently, other authors may have a selection bias that could overestimate mortality.…”
Section: Discussionmentioning
confidence: 99%
“…[11]. Universal screening for essential orthopaedic surgery in New York in April 2020 showed a 12.1% COVID-19 positive rate, which included 58.3% asymptomatic patients [12]. Computed tomography (CT) screening for urgent elective surgery in the United Kingdom reported findings suggestive of COVID-19 in 13/156 (8%) patients, and COVID-19 was confirmed in two of these patients with an additional PCR test [13].…”
Section: Discussionmentioning
confidence: 99%